Ivan Matviyovych Neklyudov and Ivan Fyodorovych Prokopenko: education and science as the meaning of life - Ponomarova, N. (New Collegium, 2022)
The article is devoted to the coverage and analysis of the main stages of the life, professional and social activities of Neklyudov Ivan Matviyovych and Prokopenko Ivan Fedorovych as leading scientists and educators by Skovoroda. I. M. Neklyudov (born in 1935), a graduater of the Faculty of Physics and Mathematics of the H.S. Skovoroda Kharkiv National Pedagogical University, doctor of physical and mathematical sciences, professor, academician of the National Academy of Sciences of Ukraine, honored worker of science and technology of Ukraine, is one of the most outstanding ukrainian physicists, whose scientific research concerns the physics of strength, physical and radiation materials science. I. F. Prokopenko (1936-2021) – Doctor of Pedagogical Sciences, professor, academician-founder of the National Academy of Pedagogical Sciences of Ukraine, honored worker of public education of Ukraine, rector of H.S. Skovoroda Kharkiv National Pedagogical University (1980 – 2020), Ukrainian economist, teacher, authoritative public figure, outstanding scientist, specialist in the field of new pedagogical technologies of education and training, economic theory, philosophy of education. I.M. Neklyudov and I.F. Prokopenko belong to a generation that has been tested by war and hard work since childhood. I. M. Neklyudov and I. F. Prokopenko, starting from graduate school to the highest management positions in the region, have passed all the steps of the great labor and scientific paths, remaining loyal to their institutions for decades. Throughout their professional careers, I. M. Neklyudov and I. F. Prokopenko performed phenomenal amounts of social, organizational and scientific work. A special place in the work of I. M. Neklyudov and I. F. Prokopenko was occupied by the leadership and training of highly qualified scientific personnel. Many years of conscientious work of I. M. Neklyudov and I. F. Prokopenko found recognition at the state level and were awarded a considerable number of awards. Thus, education in work, hardening by it, many years of daily purposeful work on oneself, steadfastness of a humanistic worldview are the keys to unconditional life and professional success of I.M. Neklyudov and I.F. Prokopenko The life and activities of I. M. Neklyudov and I. F. Prokopenko, whose main values were diligence, dedication to the profession, love for people, decency and sincerity, are not only an example to follow, but also a source of inspiration for many generations of future teachers, scientists , scientists.